Construction of Atmospheric Earth Modeling Using C++ Language - Yaseen, Waleed I.; Hassan, Malak. F. (Iraqi Journal of Science, 2023)
In this model, we use the C++ programming language to develop a program that calculates the atmospheric earth model from the surface to 250 kilometers. The balance forces theory is used to derive the pressure equation. The hydrostatic equation is utilized to calculate these parameters analytically. Variations of the parameters with altitude (density, pressure, temperature, and molecular weight) are investigated intensively. The equations for gravitational acceleration, sound speed, and scale height are also obtained. This model is used to investigate the effects of the earth's atmosphere on the space shuttle and the moving bodies inside it.